1999
DOI: 10.1016/s0006-3495(99)77301-7
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori Vacuolating Toxin Forms Anion-Selective Channels in Planar Lipid Bilayers: Possible Implications for the Mechanism of Cellular Vacuolation

Abstract: The Helicobacter pylori VacA toxin plays a major role in the gastric pathologies associated with this bacterium. When added to cultured cells, VacA induces vacuolation, an effect potentiated by preexposure of the toxin to low pH. Its mechanism of action is unknown. We report here that VacA forms anion-selective, voltage-dependent pores in artificial membranes. Channel formation was greatly potentiated by acidic conditions or by pretreatment of VacA at low pH. No requirement for particular lipid(s) was identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
189
1
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(198 citation statements)
references
References 44 publications
7
189
1
1
Order By: Relevance
“…However, in contrast to the present results, a study using isolated lysosomes suggested that vacuole formation by weakly basic substances is caused by osmotic uptake of water into organelles [6]. It has also theoretically suggested that the VacA-induced and vacuolar H + -ATPase-dependent vacuole formation is due to water influx from the cytosol to the lumen of late endosomes [21]. We sometimes observed spontaneously swollen spherical organelles, but the dif- www.fhc.viamedica.pl ferential interference contrast (DIC) image of the weak base-induced vacuoles was clearly different from that of swollen organelles: the weak base-induced vacuoles were concave, whereas the swollen vacuoles were convex.…”
Section: Involvement Of Vacuolar Hcontrasting
confidence: 99%
See 1 more Smart Citation
“…However, in contrast to the present results, a study using isolated lysosomes suggested that vacuole formation by weakly basic substances is caused by osmotic uptake of water into organelles [6]. It has also theoretically suggested that the VacA-induced and vacuolar H + -ATPase-dependent vacuole formation is due to water influx from the cytosol to the lumen of late endosomes [21]. We sometimes observed spontaneously swollen spherical organelles, but the dif- www.fhc.viamedica.pl ferential interference contrast (DIC) image of the weak base-induced vacuoles was clearly different from that of swollen organelles: the weak base-induced vacuoles were concave, whereas the swollen vacuoles were convex.…”
Section: Involvement Of Vacuolar Hcontrasting
confidence: 99%
“…These components have been demonstrated to be necessary for the vacuole formation induced by weak bases [6] and bacterial toxins, Helicobacter pylori toxin VacA [18,19,22] and Vibrio cholerae toxin [4]. The vacuolization induced by these toxins probably needs weak bases [4,21]. The weak bases are trapped in acidic organelles by intraorganelle protonation of the weak base [5,23,24].…”
Section: Involvement Of Vacuolar Hmentioning
confidence: 99%
“…In the presence of a 100-fold excess of unlabeled wild-type VacA, there was a small reduction in the binding of both the radiolabeled wild-type and mutant VacA proteins to cells at 4°C (data not shown). A high level of non-competable ("nonspecific") binding is perhaps attributable to VacA interactions with abundant cell-surface components, including anionic phospholipids (19,23). A 100-fold excess of unlabeled wild-type VacA inhibited the cellular uptake of radiolabeled wild-type and radiolabeled mutant 87-kDa VacA bands to similar extents (Fig.…”
Section: Fig 4 Structural Analysis Of Vaca-(⌬6 -27)mentioning
confidence: 90%
“…Following binding of VacA to the surface of eukaryotic cells, the toxin can insert into the plasma membrane to form anionselective channels (23)(24)(25)(26) and can also be internalized (20,27,28). Intracellular expression of VacA by transient tranfection with VacA-encoding plasmids results in the formation of intracellular vacuoles that are indistinguishable from those that form when VacA is added to the outside of cells (29,30), suggesting that this toxin acts intracellularly.…”
mentioning
confidence: 99%
“…It has been proposed that VacA toxicity requires localization of the toxin in either endosomes or mitochondria (28,32). One current model for understanding the cytotoxic effects of VacA proposes that its cell-vacuolating activity results from the formation of anion-selective channels in endosomal membranes (5,(23)(24)(25)(26). Alternatively, it is possible that VacA might have novel intracellular activities distinct from membrane channel formation (5,33,34).…”
mentioning
confidence: 99%